ANALISIS STRATEGI DAN TANTANGAN KEBIJAKAN PENGELOLAAN SAMPAH DI INDONESIA - Aini Kemala Dewi; Dymas Aditya Putra Kaharudin; Mutia Rahmah Sari; Siti Khomariah; Erinaldi (Jurnal Riset Multidisiplin Edukasi, 2025)
Waste management has become a crucial global environmental issue in the 21st century due to its significant impact on ecosystems, public health, and sustainable development. Indonesia is one of the world's largest waste producers, generating around 35 million tons of waste per year, most of which comes from the household sector. The dominant types of waste include organic waste, plastic, and hazardous and electronic waste, but only about 31.7% is successfully recycled, while the rest still pollutes the environment. This condition shows that the implementation of policies as stipulated in Law Number 18 of 2008 concerning Waste Management, which emphasizes the 3R principle (reduce, reuse, recycle), is not yet optimal. Based on data from the National Waste Management Information System (SIPSN) in 2024, the five cities with the highest waste generation are Tangerang, South Jakarta, Surabaya, Bekasi, and Medan. This study aims to examine waste management strategies and challenges in these cities through library research, an approach that traces and analyzes various literature sources such as scientific journals, reports, and official data to gain a comprehensive understanding of the effectiveness of waste management policies and innovations in urban areas. The results of this study are expected to contribute to strengthening sustainable national waste management policies based on collaboration between the government and the community.